Critical endothelial procedures during posterior lamellar graft preparation and transplantation - Fuchsluger, Thomas; Kruse, Friedrich Eduard; Geerling, G. (Ophthalmologe, 2017)
In view of the very low proliferation rate and functional importance of the corneal endothelium in maintaining corneal transparency, safeguarding the integrity of this monolayer plays a central role in posterior lamellar corneal transplantation. Several critical endothelial procedural stages are necessary to carry out such a transplantation.This article presents various preparatory and operative approaches for carrying out the necessary and critical stages within the framework of posterior lamellar corneal transplantation and concentrates on the question of optimization.A review of our own studies and studies of other groups is presented.For the performance of critical endothelial procedural steps, a variety of approaches are available. These range from preparation and insertion of the transplant, through the manipulation during centralization up to the effects of postoperative air or gas bubble tamponade.Because endothelial damage can permanently impair the integrity of lamellar transplants, a minimal handling and no touch policy should be strived for in all critical procedures. Long-term data on the follow-up course will show which of the procedures favored by various authors lead to the best postoperative results.
EVALuna2:21276